Developing The Performance Measurement System Based on Maqashid for Islamic Banks - Prasetiyo, Luhur (El-Barka, 2022)
The performance appraisal system for Islamic banks, according to the function and role of Islamic banks, is still not well established and is still in search of ideal forms. Several Islamic economic figures see that the existing Islamic bank performance appraisal system is still profit-oriented and has not considered Islamic banks' social aspects. Apart from having a business function, Islamic banks also have social functions that must be carried out. Using the maqasid al-Najjar approach, this study developed a performance measurement system based on maqashid for Islamic Banks. Using the Sekaran model, the researcher breaks down the elements of maqasid al-Najjar into indicators of performance appraisal of Islamic banks to produce a Syaria bank performance measurement system within the framework of the maqasid al-Najjar. Based on the concept of maqasid al-Najjar, the developed model in this study is called the performance measurement system based on maqashid (PMSBM) for Islamic banks.